2020
DOI: 10.1002/anie.201907525
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenolysis of Polysilanes Catalyzed by Low‐Valent Nickel Complexes

Abstract: The dehydrogenation of organosilanes (RxSiH4−x) under the formation of Si−Si bonds is an intensively investigated process leading to oligo‐ or polysilanes. The reverse reaction is little studied. To date, the hydrogenolysis of Si−Si bonds requires very harsh conditions and is very unselective, leading to multiple side products. Herein, we describe a new catalytic hydrogenation of oligo‐ and polysilanes that is highly selective and proceeds under mild conditions. New low‐valent nickel hydride complexes are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…The original reductant TMDS ( 1 H δ = 4.7 ppm) was rapidly converted into another H-donor species ( 1 H δ = 3.8 ppm) totally in seconds during the initiation period. To gain insight into this unusual transformation, combined with the results from 29 Si NMR and GC-MS (Scheme 3c), we determined that TMDS ( 29 Si δ = −5.3 ppm) was mainly converted into two parts: Me 2 SiH 2 ( 29 Si δ = −38.5 ppm) and octamethylcyclotetrasiloxane ( 29 Si δ = −19.8 ppm), 13 implying a rapid disproportionation of TMDS. Disproportionation of silanes is a common phenomenon that is considered a messy process, 14 especially the disproportionation involving a base.…”
Section: Resultsmentioning
confidence: 99%
“…The original reductant TMDS ( 1 H δ = 4.7 ppm) was rapidly converted into another H-donor species ( 1 H δ = 3.8 ppm) totally in seconds during the initiation period. To gain insight into this unusual transformation, combined with the results from 29 Si NMR and GC-MS (Scheme 3c), we determined that TMDS ( 29 Si δ = −5.3 ppm) was mainly converted into two parts: Me 2 SiH 2 ( 29 Si δ = −38.5 ppm) and octamethylcyclotetrasiloxane ( 29 Si δ = −19.8 ppm), 13 implying a rapid disproportionation of TMDS. Disproportionation of silanes is a common phenomenon that is considered a messy process, 14 especially the disproportionation involving a base.…”
Section: Resultsmentioning
confidence: 99%
“…Hydride Complexes. Hydrogen can also be used to cleave chemical bonds via hydrogenolysis. 532 Complexes 824−826 were evaluated as catalyst precursors for the hydrogenolysis of polysilanes. The catalytic hydrogenolysis of the oligosilanes H(SiPh 2 ) n H using the anionic complexes 824−826 (0.03 equiv K[Me 2 NBH 3 ], r.t., 1 bar H 2 ) quantitatively affords the monomer SiH 2 Ph 2 .…”
Section: Polysilane Hydrogenation Catalyzed By Ni(0)mentioning
confidence: 99%
“…Hydrogen can also be used to cleave chemical bonds via hydrogenolysis . Trincado and Grützmacher showed that the Ni­(I) complexes [Ni­(TFA)­(trop 2 NR)] [trop 2 NR, R = H ( 821 ), Me ( 822 ); trop = 5Hdibenzo­[ a , d ]­cyclohepten-5-yl; TFA = trifluoroacetate] react with different hydrogen sources under basic conditions (Me 2 NHBH 3 (DMAB)/KO t Bu or LiAlH 4 or H 2 /KO t Bu) to afford the Ni(0) compounds M­[NiH­(trop 2 NR)] [M = K, R = H ( 823 ); M = Li, R = Me ( 824 )] or K­[(trop 2 NR)­Ni­(μ-H)­Ni­(trop 2 NR)] [R = H ( 825 ), Me ( 826 )] (Scheme a).…”
Section: Metalates In Small-molecule Activation and Catalysismentioning
confidence: 99%
See 1 more Smart Citation